Considerations on surgery invasiveness and response and toxicity patterns in classic palliative radiotherapy for acrometastases of the hand: a hint for a potential role of stereotactic body radiation therapy? A case report and literature review - Ferini, Gianluca; Zagardo, Valentina; Viola, Anna; Aiello, Marco Maria; Harikar, Mandara Muralidhar; Venkataram, Tejas; Palmisciano, Paolo; Illari, Salvatore Ivan; Valenti, Vito; Umana, Giuseppe Emmanuele (Frontiers in Oncology, 2023)
Background: The rarity of hand acrometastases hampers the consensus-building for their optimal management among the involved oncology professionals. In the current literature, demolitive surgery overcomes the use of palliative radiotherapy, which proved to be ineffective in more than 30% of cases treated with classic palliative dose schemes, carrying also a not negligible radiation-related adverse event rate. Against this background, stereotactic body radiation therapy (SBRT) could emerge as a well-balanced therapeutic option. Case Summary: Here, we describe the methods and outcomes of a SBRT treatment of a painful and function-limiting hand acrometastasis in a patient with a history of stage IIIB lung adenocarcinoma. We delivered a total dose of 30 Gy in five daily fractions to a soft-tissue metastasis abutting the fifth metacarpal bone through the SBRT protocol generally used for intracranial treatments. A few weeks later, the patient reported a clinical complete response with acrometastasis and pain disappearance, function recovery, and no significant toxicity. The acrometastasis was the first sign of an atypical cancer progression. Conclusions: SBRT for hand acrometastases is feasible and might have the best therapeutic profile among the currently available treatment options for this rare clinical scenario. Larger investigations are needed to confirm the present single-case experience.